Legal Framework for Protecting The Rights of Internally Displaced Persons in Ukraine During The War - Tesliuk, Iryna; Pogrebnyak, Olena; Kozariichuk, Dmytro; Matsko, Vita; Khoroshun, Оleksandr (Syariah: Jurnal Hukum dan Pemikiran, 2023)
The research aims to uncover the legal regulation of the status of internally displaced persons in Ukraine during the war. A positive step for realizing the rights and guarantees of forced migrants consists in introduction by the Government of Ukraine of the following areas of assistance: monetary assistance, promotion of their employment, introduction of compensation for the costs of paying for communal services for families who sheltered displaced persons free of charge.  The specifics of the research subject, as well as its purpose and tasks determined the use of general scientific and special methods of scientific cognition. It has been established that an extremely important role in exercising rights and guarantees of forced migrants belongs to such a public initiative as “Prykhystok” (“Shelter”). The problems of ensuring the rights and freedoms of internally displaced persons by state authorities in Ukraine are systematized, including: uncertainty of competence and lack of consistency in the activities of state authorities regarding the provision of rights and freedoms of internally displaced persons in Ukraine; imperfect accounting of internally displaced persons and their needs; lack of a strategy for state financial provision of the needs of internally displaced persons.